2006
DOI: 10.1111/j.1464-5491.2006.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term benefits of continuous subcutaneous insulin infusion in children with Type 1 diabetes: a 4‐year follow‐up

Abstract: In this population of selected patients in our clinic, CSII appears to be a safe and effective therapeutic alternative to MDI treatment. This therapy may ensure a stable improvement in long-term glycaemic control in paediatric patients, with no increase in diabetic ketoacidosis and severe hypoglycaemic events and, on the other hand, with a trend of reduction in BMI z scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 31 publications
2
50
2
1
Order By: Relevance
“…However, it remained 0.3% (3.3 mmol/mol) lower than in the matched non-pump cohort. Sulli and Shashaj also noted a trend for the mean HbA 1c to increase at 2 years before improving for the next 2 years of their study [4]. This may be partly due to waning enthusiasm for the new technology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it remained 0.3% (3.3 mmol/mol) lower than in the matched non-pump cohort. Sulli and Shashaj also noted a trend for the mean HbA 1c to increase at 2 years before improving for the next 2 years of their study [4]. This may be partly due to waning enthusiasm for the new technology.…”
Section: Discussionmentioning
confidence: 95%
“…associated with pump therapy [3][4][5], although some report no improvement or an initial improvement followed by a return to pre-pump levels after a short time [6][7][8][9]. Reports have also suggested that insulin pumps may be associated with a reduction in severe hypoglycaemia [3,10,11].…”
mentioning
confidence: 99%
“…The use of insulin pumps in the pediatric diabetes population is rapidly increasing [1][2][3][4] and is approaching 35% in Sweden. 5 When starting with an insulin pump, the basal rate and bolus doses are calculated from the current dose on injection therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A eficácia e a segurança do uso da bomba de insulina na população pediátrica, mesmo abaixo de 6 anos, é confirmada por outras publicações recentes que mostram ainda outras vantagens dessa modalidade terapêutica, como redução da A1c, promoção de controle metabóli-co adequado sem aumento nas taxas de ocorrência de hipoglicemia e cetoacidose, além da tendência de redução no índice de massa corpórea (24)(25)(26).…”
Section: Uso De Bomba De Insulina Em Criançasunclassified